Application of New Renewable Energy Sources while Rehabilitating Radionuclide Contaminated Territories of the Republic of Belarus - Yu. А. Losiuk,; A. M. Zaborovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers one of the approaches to rehabilitation of radionuclide contaminated territories of the Republic of Belarus. In accordance with the proposed method it is possible to produce ecologically clean product on the lands affected by the Chernobyl accident that is electric power with application of renewable energy sources such as solar energy, wind and biomass.